2009
DOI: 10.1021/la901924z
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nanofiber Deposition through Field-Enhanced Electrospinning

Abstract: In this paper, we demonstrate a nanofiber patterning technique using field-enhanced electrospinning. Polyethylene oxide (PEO) nanofibers were electrospun on an elastomeric substrate with gold-coated pyramidal protrusions with the majority of fibers being deposited at the tips. The deposited nanofiber spots ranged from 8 x 8 microm(2) to 60 x 60 microm(2) in size, uniformly covering an area of 5 x 10 mm(2). Our experiments also indicate that nanofiber pattern selectivity is highly dependent on the separation/si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 14 publications
1
80
0
Order By: Relevance
“…Besides the two strategies mentioned above, more improvements such as conductive temp late method [66,67], centri fugal electrospinning [68−70], and n ear-field electrospinning methods [71−74] have also been developed. Conductive template method can be used to prepare NWs with complex ordered architectures and patterns [67].…”
Section: Near-field Elec Trospinning Methods and Other Modificationsmentioning
confidence: 99%
“…Besides the two strategies mentioned above, more improvements such as conductive temp late method [66,67], centri fugal electrospinning [68−70], and n ear-field electrospinning methods [71−74] have also been developed. Conductive template method can be used to prepare NWs with complex ordered architectures and patterns [67].…”
Section: Near-field Elec Trospinning Methods and Other Modificationsmentioning
confidence: 99%
“…Another technique called field-enhanced electrospinning has been reported to assemble and pattern as-spun fibers. 166 Polymer fibers were spun on an elastomeric substrate with gold-coated pyramidal protrusions with majority of fibers being deposited at the tips, and nanofiber pattern selectivity is highly dependent on the separation/size ratio of the pyramidal protrusions with a ratio of o1. …”
Section: Conductive Template Chang's Groupmentioning
confidence: 99%
“…Figure 3 shows a variety of collectors and their effect on the nanofiber mat pattern. Ding et al recently demonstrated the selective deposition of nanofibers on an elastomeric substrate containing gold-coated pyramidal spikes [69]. Star and radial fiber patterns have also been prepared using enamel patterned steel-sheet collectors [70].…”
Section: Patternsmentioning
confidence: 99%